On the effects of L2 aptitude, phonological short-term memory, and L2 motivation on L2 listening performance - Véliz-Campos, Mauricio; Cerda-Oñate, Karina; Biedroń, Adriana; Rojas-Barahona, Cristian A.; Veliz, Leonardo (Neofilolog, 2024)
L2 learning is influenced by both individual learner variables and contextual factors. Contextual factors have been extensively researched, but although internal learner-specific variables have received attention, this has been to a lesser extent. Among these internal variables, L2 motivation and L2 aptitude are likely the most significant predictors of L2 learning progress and listening performance. This study explored the effects of (i) L2 motivation, following the L2 Motivational Self-System model; (ii) L2 aptitude; and (iii) phonological short-term memory (PSTM) on L2 listening performance. These variables combined have not yet been studied with reference to L2 listening. In this correlational study, a listening test was taken as a pre- and post-test in a sample of 104 Year 1 and Year 2 English language pre-service teachers from a Chilean University three months apart. L2 aptitude and PSTM measures were taken using the first two sections of the Modern Language Aptitude Test (MLAT) for the former variable, and a non-word repetition task for the latter. The results suggest that PSTM, but not L2 aptitude, predicted listening performance at time 2. Also, the results indicate that after adjusting for listening performance at time 1, the only motivational factor predicting listening performance at time 2 was learning experience.